Psychometric Characteristics Of The Statistical Self-Efficacy Scale Among Trainees At College Of Technology In Abha - Teleb, Ahmed Ali; Alqhtani, Hussein Muhammed (Migration Letters, 2024)
The current research aims to build a measure of statistical self-efficacy among College of Technology trainees, and to verify its psychometric efficiency. The statistical self-efficacy scale in its final form consists of (50) items. The scale was applied to (152) trainees at College of Technology in Abha, and their average chronological age was 30.26 years with a standard deviation of .75. The validity of the scale was verified using the content validity and construct validity, and the internal consistency of the sub-dimensions and the scale as a whole was verified. The findings of the exploratory factor analysis after orthogonal rotation using the Varimax method and the Kaiser test resulted in the presence of four main factors: Preparation efficacy, which consists of (6) items, application efficacy, which consists of (22) items, the efficacy of reading and analyzing the results, which consists of (17) items, and interpretation efficacy, which consists of (5) items. The results of the confirmatory factor analysis confirmed what was reached through the exploratory factor analysis, as the results showed that the goodness-of-fit indicators for the confirmatory model were within acceptable limits. In addition, standard saturation values were all greater than (.5) and all of them were statistically significant (p<.01). The reliability of the scale was also verified by using Cronbach’s Alpha and split-half, whether for the sub-dimensions or for the scale as a whole.